Pyrolysis of plastic waste for production of heavy fuel substitute: a techno-economic assessment - Fivga, Antzela; Dimitriou, Ioanna (Elsevier, 2018)
Pyrolysis is widely seen as a promising technology for converting plastic waste into a wax/oil product which can be used as a heavy fuel oil substitute or as raw material by the petrochemical industry. A pyrolysis plant with a capacity of 100 kg/h plastic waste is modelled in the process simulation software Aspen HYSYS. The production costs of the pyrolysis fuel product is estimated at £0.87/kg which is 58% higher than current market prices; therefore, a scaling-up analysis is also carried out to determine the plant capacity for which the pyrolysis process is economically feasible. The fuel production costs of the scaled-up cases considered are approximately 2.2–20.8 times lower than the existing market prices of residual fuel oil, indicating their economic feasibility. For the 1000 kg/h and 10,000 kg/h plant capacity cases the facility needs to operate approximately four years and one year respectively, to recover the capital investment, while the 100,000 kg/h case produces revenue and has a positive NPV within year one. A sensitivity analysis is also carried out revealing that the fuel production rate is the most sensitive parameter for the 100 kg/h plant, as well as the scaled-up plants.